INVESTIGATION OF PHASE CHANGE MATERIAL WITH/WITHOUT ALUMINIUM PLATE FOR BATTERY THERMAL MANAGEMENT (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Concerns about global warming related to carbon emissions increased interest in electric vehicles (EVs). The current EV technology requires development on fast charging and battery lifetime increment, which require strict temperature control. This study investigated the effectiveness of implementing phase change material (PCM) for battery thermal management with/without an aluminum plate. Initially, a 73 Ah NMC pouch cell was discharged in an insulated environment at a 1°C rate to record the behavior of the battery. Then, a PCM pack is inserted into the cell during discharge. Finally, an aluminum plate with 0.5 mm thickness is inserted between the battery and the PCM pack to uncover the effect on the thermal behavior. To reveal the impact of the experiments, temperature measurements are taken from the upper surface (near positive and negative tabs) and bottom surface of the battery. Results show that the maximum temperature decreases, and temperature uniformity increases with PCM (with/without an aluminum plate) relative to the base case. The temperature difference between the two sides of the battery was measured as 4.3°C, 1.1°C, and 1.2°C for the base case, with the PCM pack and the PCM pack and aluminum plate, respectively. Even though the net temperature differences do not reflect the increased temperature homogeneity achieved with the added aluminum plate, the data set is helpful. In the end, the results of these experiments successfully demonstrated that using PCM is helpful in the thermal management of batteries and that using conductive layers can improve the battery’s thermal uniformity.
Keywords: Battery thermal management; Phase change materials; Passive cooling